STAGES OF THE EARLY TRIASSIC AMMONOID EVOLUTION IN THE EASTERN BOREAL PROVINCE - Ermakova S.P. (My University, 1999)
The history of the evolution of the Early Triassic ammonoid communities in the eastern Boreal province is discussed with due regard for the peculiarities of their biogeographic differentiation and phylogenetic relations. The evolution is shown to include two rhythms of fauna development in the Induan and Olenekian stages, four stages, and 11 phases corresponding to 22 zones and subzones of the biostratigraphic zonation of the Lower Triassic in southeastern Asia.
Keywords: Triassic; Mesozoic::Triassic; Мезозой::Триасовая